Paciente masculino de 63 años con enfermedad pulmonar obstructiva crónica. - Arellano Zambrano, Oscar Enrique (2022)
Chronic obstructive pulmonary disease is defined as a pathophysiological process, which is characterized by limiting the flow of air to the lungs, in most cases progressively, its symptomatology of chronic obstructive pulmonary disease is usually accompanied by persistent respiratory symptoms that limit the exchange of gases in the pulmonary alveoli, one of the most relevant etiologies is the consumption of tobacco and exposure to gases such as carbon monoxide which are found in the burning of different types of materials of daily use in the life of the people. The world health organization classifies it as one of the most frequent respiratory pathologies in the world with a high mortality rate, which reached the third place in number of deaths in 2020, it is a disease of relevance for the public health system. at the national level because it generates great need in the socioeconomic, medical, and social. The objective of the study is to recognize the clinical picture in the patient to provide an optimal treatment that guarantees their survival. The main symptoms are: shortness of breath, throat clearing, sputum, and wheezing. The main cause is long-term exposure to irritating gases and by inhaling cigarette smoke, as well as its consumption. The exacerbation of COPD is a serious episode, where the symptoms increase. Complications such as impaired lung function, further progression of the disease and increased morbidity and mortality may appear.